(untitled) (Bangladesh Journal of Nutrition, 2013)
This cross-sectional comparative study was conducted in Muradnagar Upazila, Comilla district to see the effectiveness of NNP-ABCN (Area Based Community Nutrition) interventions on reducing under-two child malnutrition (0-23 months) and establish whether there is any significant difference from the non-operational area. A total of 240 households, of which 120 were from the NNP project area with children aged between 0-23 months were randomly selected. In households with more than one child at this age category, the last child was selected. Indices of nutritional status that is weight-for-age, length-for-age and weight-for-length were computed for the measurement of nutritional status. Analysis of nutritional status data show that the prevalence of underweight (<-2SD) in the project area (35.8%) was slightly lower than the non-project area (39.2%) with severe underweight being 5.0% vs. 7.5% respectively. Within the project sample, 32.5% children were stunted (<-2SD) with 11.7% being severely stunted while in non-project area these figures were 33.3% and 7.5% respectively. On the other hand, 17.5% children were wasted (<-2SD) with 2.5% being severely wasted in project area while in non-project area these figures were 19.2% & 1.7% respectively. No significant differences in the prevalence of stunting, wasting and underweight (<-2SD) between the project area and non-project area (WAZ, p=0.078; LAZ, p=0.214 & WLZ, p=0.421) were found. The study area and sample size arent large enough to draw any conclusion still this is an indication that NNP-ABCN interventions may not be effective in reducing under two child malnutrition in study area. Even though NNP has been involved in providing ABCN interventions in the project area, there is still need for more targeted and income oriented nutrition interventions in the project area. Large scale operational research is thus suggested to adopt those findings for the whole NNP areas. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14040 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.93-106